Assessment of expected reliability of applied software for computer-based information systems - S. M. Borovikov; V. O. Kaziuchyts,; V. V. Khoroshko; S. S. Dick; K. I. Klinov (Informatika)
The reliability of computer-based information systems is largely determined by the reliability of the developed application software. The failure rate of its computer program is considered as an indicator of the reliability of the application software. To determine the expected reliability of the application software planned for the development (until writing the code of a program), the model is proposed that uses some parameters of the future computer program, data on the influence of various factors on its reliability, and further testing of the program. The model takes into account the field of software application and computer processor performance. The process of model parameters obtaining is analyzed., It is possible by use of proposed model to determine the predicted failure rate of the planned application computer program, and then the reliability of the computer-based information system as a whole. If necessary, the measures can be developed to ensure the required level of reliability of the computer-based information system.